2020
DOI: 10.3917/spub.204.0381
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs associés à l’autonomie de décision des femmes pour leur santé au Sénégal

Abstract: Introduction : Au Sénégal, la problématique de l’accès aux services de santé maternelle, reproductive et sexuelle demeure une priorité sanitaire. Malgré de nombreuses interventions sanitaires, l’accès des femmes aux services de santé reste limité du fait de leur faible autonomie concernant les décisions pour leur santé. But de l’étude : L’objectif de cette étude était d’étudier les facteurs associés à l’autonomie décisionnelle des femmes par rapport à leur santé au Sénégal en 2017. Résultats : Moins d’une femm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This could be explained by the fact that older women have more experience in several areas of life and gain awareness and trust from their partners over time. These results confirm those identified in the work of Abbas, Akram, and Sougou [10,12,27]. Marital status also influences decision-making.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This could be explained by the fact that older women have more experience in several areas of life and gain awareness and trust from their partners over time. These results confirm those identified in the work of Abbas, Akram, and Sougou [10,12,27]. Marital status also influences decision-making.…”
Section: Discussionsupporting
confidence: 90%
“…However, Castro Lopes et al [9] in Mozambique and Abbas et al [10] in Pakistan reported that age, level of education, womenʹs occupation, and wealth index impact women's decision-making power. Belachew et al [11] in Ethiopia and Sougou et al [12] in Senegal also reported that age, educational level, religion, womenʹs residence in urban areas, and media exposure determine autonomy in the use of contraceptives. These factors cannot be extrapolated to Congolese women who may have different social and environmental contexts.…”
Section: Introductionmentioning
confidence: 98%
“…They have decision-making autonomy regarding their bodies, including reproductive health. Therefore, this condition leads to better family planning behavior [37]. However, women living in urban areas were mostly independent of socioeconomic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the notion of autonomy was also linked to the women's decision-making power inside their household, and the influence of people living with them (Matsumura and Gubhaju, 2001). This was also evidenced in Chaka's (2019) systematic review and in studies based in Senegal, Mali and south Asia (Senarath and Gunawardena, 2009;Sougou et al, 2020;White et al, 2013). Indeed, a majority of Nepalese women were not able to make decisions about their own health due to the influential position of their partner or family (Senarath and Gunawardena, 2009).…”
Section: Discussionmentioning
confidence: 99%